Prawa dziecka w percepcji nastolatków: przykład badania psychologicznego i tworzenia programów edukacyjnych = The adolescences representations about child's right: experience of psychological study and design of educational programs - Černaa, Anna V. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main thesis of this article is that Child right and Human Rights Education (HRE) leads to a culture of human rights of teenagers. The article describes an experience of empirical research children's rights overview in 3 groups of teenagers 10-11, 12-13, 14-15. Short review described Worldwide child rights initiatives, researches as well as analysis of the key ideas of human rights education (HRE). We discuss the quantitative and qualitative results of the study with the author's express questionnaire "The Child Right Overview". The thesis about how we can involved of research results into child rights educational programs was discussed.
Keywords: prawa dziecka; edukacja w obszarze praw dziecka; programy edukacyjne; child rights; overview on the Child Rights; Child Rights Education; educational programs in the child rights